Evaluation of Factors Influencing Thigh Circumference Measurement in Dogs - Ana Luisa Bascuñán; Nina Kieves; Clara Goh; Juliette Hart; Penny Regier; Sangeeta Rao; Sasha Foster; Ross Palmer; Felix Michael Duerr (Veterinary Evidence, 2016)
Objective: To evaluate inter- and intra-observer variability, influence of hair clipping and laser guidance on canine thigh circumference (TC) measurements amongst observers. Background: It was our goal to further study the reliability of canine TC measurements as currently performed. For this purpose we designed a cadaveric model that allows for controlled inflation of the thigh resembling increase of muscle mass. We also investigated the impact of novel technologies (laser guidance) and hair clipping on TC measurements in this model. Evidentiary value: Phase 1 cadaveric study - five long-haired, large breed canine cadavers; Phase 2 clinical study - eight clinically healthy Golden Retrievers. This study should impact clinical research and practice. Methods: Phase 1 - Canine cadaveric thigh girth was manually expanded to three different levels using a custom, submuscular inflation system before and after hair clipping; Phase 2 - TC of Golden Retrievers was measured with and without laser guidance. TC measurements for both phases were performed by four observers in triplicate resulting in a total of 552 measurements. Results: Phase 1 - TC measurements before and after hair clipping were significantly different (3.44cm difference, p<0.001). Overall inter-observer and intra-observer variability were 2.26±1.18cm and 0.90±0.61cm, respectively. Phase 2 - Laser guidance nominally improved inter-observer variability (3.34 ±1.09cm versus 4.78 ±2.60cm) but did not affect intra-observer variability (1.14 ±0.66cm versus 1.13 ±0.77cm). Conclusion: TC measurement is a low fidelity outcome measure with a large inter- and intra-observer variability even under controlled conditions in a cadaveric setting. Current methods of canine TC measurement may not produce a valid outcome measurement. If utilised, hair coat clipping status should be considered and an intra-observer variability of at least 1cm should be assumed when comparing repeated TC measurements. Laser guidance may be helpful to nominally reduce inter-observer variability in settings with multiple observers. Further investigation of alternative methods for canine TC measurement should be pursued. Application: This information should be considered by everyone utilizing TC measurements as an outcome assessment for clinical or research purposes.